An extension of UML activity graph meta-model based on the workflow meta-model - Acosta, Edgardo (2002)
The WfMC (Workflow Management Coalition) proposed an standard to unify the format of the definitions of workflow processes. Such standard is defined by a basic meta-model and a language for workflow process definition (WPDL) based on the same meta-model. On the other hand, the UML activity graph notation is used to model a business process, but it has a certain level of abstraction. Some details can not be modeled, others can represent ambiguities and/or inconsistencies. Therefore, a process specification based on activity graphs can not satisfy the standard of the WfMC. We propose an extension of the activity graph to overcome this deficiency without modifying the UML standart. The models based on this extension will be easily translated to the standard of Workflow. In this paper we show the extension of the UML activity graph meta-model for workflow activities and in particular for Implementation and Subflow activities. We chose this entity because it extension is a good examples of how the Workflow meta-model extends the expressive power of UML activity graph and reduce it ambiguity.